The Role of oversight in bringing administration stability at Mpofana Local Municipality - Boyce, Nontembeko Nothemba (University of the Witwatersrand, Johannesburg, 2024)
This thesis explores the complex dynamics of governance within the South African public sector, focusing on oversight mechanisms within the Mpofana Local Municipality. Against the backdrop of persistent challenges hindering stability and effective governance, the study seeks to uncover the underlying factors contributing to prolonged instability despite intervention. Notably, the Mpofana Local Municipality situated in the KwaZulu-Natal province, has been under Section 139(1)(b) intervention for over six years since December 2018, following years of governance struggles related to service delivery challenges and fiscal mismanagement. I argue that the persistent instability and governance challenges in the municipality despite prolonged intervention, stem from a complex interplay of inadequate legislative and regulatory frameworks, detrimental intra-party politics within the African National Congress, and a lack of focus on critical socioeconomic factors. Employing a qualitative case study approach, I conducted an in-depth analysis of legislative documents, municipal reports, and academic literature, complemented by 15 semi-structured interviews with key stakeholders including municipal officials, council members, and community representatives. This approach facilitated a nuanced exploration of the multifaceted nature of local governance and the specific challenges faced by the Mpofana Local Municipality. The findings reveal significant gaps in the legislative framework guiding Section 139 interventions, highlighting the need for standardised legislative clarity to enhance governance efficacy. Furthermore, the research identifies the detrimental impact of ANC intra-party politics on municipal governance, underscoring the need for political neutrality in administrative processes. Lastly, the study emphasises the importance of addressing the socioeconomic underpinnings of governance challenges, advocating for integrated solutions that consider the broader socio-economic landscape. By situating the Mpofana Local Municipality governance issues within broader political governance and public administration debates, the study contributes to the discourse in public administration and governance by proposing a holistic approach to oversight mechanisms, emphasising the need for refined legislative frameworks, political neutrality in governance processes, and the integration of socioeconomic considerations into governance strategies, thereby suggesting a roadmap for enhancing governance stability and effectiveness in local government settings.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; administration stability; Mpofana Local Municipality; SDG-8: Decent work and economic growth